Innovations in the exploitation of Geothermal Energy - Barbosa Lima, Leandro Jose (Revista Ciências Exatas, 2025)
While the demand for energy grows worldwide, the world depends on 80% of fossil fuels, which produces greenhouse gases and air pollutants, to generate electricity. Solar and wind energy represent a good opportunity, but these are energies dependent on nature and are not available throughout the day or periods of the year at the same intensity. Geothermal energy is, virtually, infinite, and available, at different depths, anywhere in the world, but it involves a high cost of well construction and production plant. This study, based on a systematic review of the literature, presents innovations ranging from alternatives for reusing oil wells for geothermal exploration to the standardization and automation of the drilling process. These can make geothermal energy economically viable and available